Experimental study on water-exit of cylinder - Yun, Honglu; Liu, Qingbo; Zeng, Zheng; Lian, Lian (Ocean engineering, 2024)
In this paper, the hydrodynamic characteristics of the cylinder water-exit are studied by high-speed camera experiments. The characteristics of cylindrical motion trajectory, velocity and acceleration are analyzed by image processing algorithm. The emission voltage (i.e. initial velocity) and emission depth are important influencing factors. Based on different emission voltage and depth, the hydrodynamic coefficient is compared and analyzed. The results show that the new research method has good adaptability to the experimental study of cylindrical water-exit. The emission voltage directly affects the initial velocity of the cylinder, which in turn affects the force changes during the water exit process. The increase in emission depth exacerbates the uncertainty of the moment when the cylinder exits the water, thereby affecting the changes in the wake and motion stability during the cylinder water exit process. •New advanced experimental research methods have been applied to the study of water exit problems.•The emission voltage and depth directly determine the stability of the water exit process.•The kinematic and mechanical characteristics of a cylindrical water exit are analyzed.